Comparison of the Sense of Coherence between Mothers with Healthy Children and Mothers of Children with Chronic Disease in Kerman - Nosrat Avaznejad; Maryam Ravanipour; Maryam Ravanipour; Nilofar Motamed (Kerman University of Medical Sciences, 2016)
Introduction: Children with chronic disease make some problems in the family that have negative effect on the family members' quality of life, especially mother's. Promoting the sense of coherence and capability of mothers to adapt and manage the problems of children with chronic disease and their family seems necessary. Methods: This descriptive-analytical study was performed on 300 women (150 mothers with healthy children and 150 mothers of children with chronic disease). Convenience sampling was used for mothers of children with chronic disease, and random sampling for mothers of healthy children. Data were collected using the valid and reliable Antonovsky's sense of coherence scale. Data were analyzed using descriptive statistics (the frequency, mean, standard deviation) and analytic statistics (Pearson's correlation coefficient and Mann-Whitney U test) by SPSS 18. Results: There was a significant difference in the total score of mothers' sense of coherence between the groups. There was also a significant difference in the three components of mothers' sense of coherence (comprehensibility, manageability, and meaningfulness), so that mothers with healthy children had higher scores in all cases (P=0.0001). Conclusion: It seems that a comprehensive program of empowerment that promotes the mothers' sense of coherence, can be very effective in reducing the problems of compatibility, management, and care of mothers of children with chronic disease, and subsequently, promotes the Health-related quality of life (HRQOL) in family members. Keywords: Sense of Coherence, Mother, Chronic Disease, Healthy Children, Children with Chronic Disease, Atonovesky's Questionnaire Citation: Avaznejad N, Ravanipour M. Bahreini M, Motamed N. Comparison of the Sense of Coherence between Mothers with Healthy Children and Mothers of Children with Chronic Disease in Kerman. Journal of Health Based Research 2016; 2(2): 183-196.